Multi-band behaviour of the TeV blazar PG 1553+113 in optical range on diverse timescales. Flux and spectral variations - Agarwal, A. (2020)
Context. The TeV BL Lac object PG1553+113 is one of the primary candidates for a binary supermassive black hole system.Aims. We study the flux and spectral variability of PG1553+113 on intra-night to long-term timescales using (i) BVRI data collected over 76 nights from January 2016 to August 2019 involving nine optical telescopes and (ii) historical VR data (including ours) obtained for the period from 2005 to 2019.Methods. We analysed the light curves using various statistical tests, fitting and cross-correlation techniques, and methods for the search for periodicity. We examined the colour-magnitude diagrams before and after the corresponding light curves were corrected for the long-term variations.Results. Our intra-night monitoring, supplemented with literature data, result in a low duty cycle of ∼(10?18)%. In April 2019, we recorded a flare, which marks the brightest state of PG1553+113 for the period from 2005 to 2019: R ≃ 13.2mag. This flare is found to show a clockwise spectral hysteresis loop on its VR colour-magnitude diagram and a time lag in the sense that the V-band variations lead the R-band ones.We obtain estimates of the radius, the magnetic field strength, and the electron energy that characterize the emission region related to the flare.We find a median period of (2.21±0.04) years using the historical light curves. In addition, we detect a secondary period of about 210 days using the historical light curves corrected for the long-term variations. We briefly discuss the possible origin of this period.